(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This work postulates the existence in Iberian of a glottal stop used as a mark in prosodic boundaries, which would have developed a secondary nasalization in the surrounding low vowels, according to the phenomenon described by Matisoff 1975 and named by him “rhinoglottophilia”. These nasalized vowels would occasionally be represented by Y. The sign m in final position could represent an allophone of the only Iberian nasal phoneme in this boundary position before a glottal stop. Most infixes between onomastic compounds, as well as the bisyllabic variants of monosyllabic onomastic elements, could be explained as representations of this glottal sound, of its associated nasalization, or else as pseudo-prefixes originated by a shift to bisyllabism. In Aquitanian the glottal stop would have an initial lenis allophone, the voiceless glottal fricative.